A novel case using femtosecond laser-acquired lenticule for recurrent pterygium: case report and literature review. Issue 6 (June 2018) - Pant, Om Prakash; Hao, Ji-long; Zhou, Dan-dan; Wang, Fan; Lu, Cheng-wei
Small incision lenticule extraction (SMILE) is a minimally invasive, safe and flapless femtosecond laser technique used mainly to correct myopia through extraction of a corneal lenticule. Lenticules obtained in this way are transparent and of high quality, and thus, can be used to treat other corneal diseases. A 65-year-old male patient presented with recurrent pterygium complicated by thin cornea. The patient was treated surgically using a SMILE-extracted lenticule to avoid further complications and to maintain eyeball integrity. The lenticule was sutured over the thin section of cornea using 10-0 interrupted nylon sutures and enclosed by a single layer of amniotic membrane. The patient was evaluated using slit-lamp biomicroscopy and anterior-segment optical-coherence tomography. During an 8-month follow-up, the graft remained intact with no sign of rejection and corneal thickness was maintained. Tectonic keratoplasty using a SMILE-extracted lenticule appears to be a safe, cost-effective and reliable method for treating thin cornea due to repeated surgeries for recurrent pterygium. This is the first case of recurrent pterygium complicated by thin cornea managed surgically using a SMILE-extracted lenticule.